Building Organizational Performance through Strategic Visionary Leadership and Total Quality Management: An Organizational Excellence Framework - Satria Avianda Nurcaho; Pipit Sundari; Yeni Indraningtyas; Teguh Harso Widagdo; Ahmad Ali (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Organizational performance has become a critical determinant of sustainable competitiveness in the Islamic banking industry amid rapid digital transformation, increasing customer expectations, and evolving regulatory demands. Although Strategic Visionary Leadership (SVL) and Total Quality Management (TQM) have been widely recognized as important organizational capabilities, empirical evidence integrating both constructs within an organizational excellence framework remains limited, particularly in Islamic banking. This study aims to examine the effects of Strategic Visionary Leadership and Total Quality Management on Organizational Performance and to develop an Organizational Excellence Framework for PT Bank Syariah Indonesia (BSI) Regional Central Java. Grounded in the Resource-Based View (RBV) and Dynamic Capability Theory, this research proposes that visionary leadership provides strategic direction, inspires innovation, and enhances organizational adaptability, while Total Quality Management strengthens operational effectiveness through continuous improvement, customer focus, employee involvement, and process excellence. A quantitative explanatory research design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through structured questionnaires distributed to managers and employees of PT Bank Syariah Indonesia Regional Central Java using purposive sampling. Organizational Performance was measured through financial and non-financial indicators, including operational efficiency, service quality, customer satisfaction, employee productivity, innovation capability, and organizational sustainability. The proposed model examines the direct effects of Strategic Visionary Leadership and Total Quality Management on Organizational Performance and their complementary contribution to organizational excellence. The findings are expected to demonstrate that Strategic Visionary Leadership positively influences Organizational Performance while simultaneously strengthening the implementation of Total Quality Management. Furthermore, Total Quality Management is expected to significantly enhance Organizational Performance by improving service quality, operational efficiency, and organizational learning. The integration of these two strategic capabilities provides a comprehensive Organizational Excellence Framework capable of generating sustainable competitive advantage in Islamic banking. This study contributes to the literature by extending the understanding of the relationship between leadership and quality management within an integrated strategic framework. Practically, the findings offer valuable insights for executives of Islamic banks in designing leadership development initiatives and implementing quality management practices that support long-term organizational excellence, resilience, and superior organizational performance in an increasingly competitive financial environment.